Implementasi Peraturan Daerah Kota Medan Nomor 6 Tahun 2003 Tentang Gelandangan dan Pengemisan Serta Praktek Tuna Susila - Sahara Angriani Siregar; Abdul Kadir; Beby Masitho Batubara (Universitas Medan Area, 2021)
Sprawl is an issue that must be faced by the government especially the social city of medan, because of sprawl have been considered as a profession pekerajaan that easy, even want to be criminal and disturb the comfort of society as well as interfere with riders with how to write with a windshield. This is a task of the city of medan to services vagabonds and beggars in the city of medan. The research is to determine the extent the implementation of the regulatio ns the city of medan, number 6 years 2003 and anything that is in their implementation. The method used is the method of quantitative, researchers used the theory of Edward III said that fator the implementation of communication, resources, disposition, and the structure of bureaucracy. The results of the investigators are social services has served her purpose in accordance with the theory, the researchers just not optimally and there are obstacles faced and that is the lack of awareness which is owned by the community in providing something and be seen from the resources there is still a shortage of facilities and infrastructure in the implementation of, such as the absence of safe houses and the lack of a patrol car owned. To the city of medan should ask the revision of regulations number 6 in 2003, in order to be more effective and rational in answering the problems sprawl in the city of medan and be able to meet the needs of facilities and infrastructure to the implementation of the running on as planned.